O Mas na Produção Textual: uma análise semântico- discursiva - Silva, Marcos Antonio da (2010)
This research is based on the Argumentation Theory in Language, it was proposed by Jean-Claude Anscombre, Ducrot et al, for whom the language is argumentative in nature. The Argumentation Theory is centered on the fact that some words have argumentative values which are responsible for the possibility or impossibility of continuing within the discourse. Ducrot called some of those words of argumentative operators and he affirms the operators behave as constituents of the internal structure of utterance. Ducrot and Vogt distinguish two types of mas: a masPA which has argumentative function and a masSN which serves to refute or correct something said earlier. Our purpose in this research is to analyze and describe the functioning of semantic-discursive operator mas in a corpus of textual production by 139 former students in high school, produced during the achievement of SERIES SELECTION PROCESS (PSS 2009) from Federal University of Paraíba (UFPB). At the end of the analysis, according to the proposed objectives and also achieved, it is pertinent to affirm that students use predominantly the operator masPA than the masSN. The operator masPA works not only for guiding statements to contrary conclusions, but also to conclusions which, to some extent, are complemented.